Association of Short term Outcomes of Acute Coronary Syndrome with Prediabetes (Bangladesh Journal of Medical Biochemistry, 2018)
The global incidence and prevalence of prediabetes are rapidly increasing with a parallel increase in the proportion of patients suffering from acute coronary ischemic events with prediabetes. Impaired glucose metabolism (IGM), comprising impaired glucose tolerance and impaired fasting glycemia (IFG), is also associated with an increase risk of Acute coronary syndrome (ACS). This study was aimed to assess the adverse outcomes of Acute Coronary Syndrome (ACS) with and without prediabetes. This prospective observational study was conducted with 132 patients admitted in coronary care unit and cardiology departments of Dhaka medical college and NICVD, Dhaka from January 2010 to December 2010. The patients were grouped into prediabetic ACS group (Group A) and non-diabetic ACS group (Group B) by estimating fasting blood glucose and 2 hours postparandial blood glucose. Mean (±SD) age of prediabetic ACS group (56.73±8.19 years) was higher than non-diabetic ACS group (53.16±8.92 years) and it was statistically significant. In this study 85 (64.4%) patients were male and 47 (35.6%) patients were female. The presence of risk factors, such as smoking (65.9% vs 48.9%), dyslipidemia (86.4% vs 68.2%), family history of IHD (20.5% vs 14.8%) and hypertension (65.9% vs 43.2%) was higher in group A study subjects in comparison to group B. Overall final outcome results of study subjects during hospital stay in group A and group B respectively were heart failure 14 (31.8%) and 10 (11.4% (P